Export economy and development in China: the domestic takeover of high-tech exports and the “Made in China 2025” - Vasconcelos, Daniel de Oliveira (Seminário Pesquisar China Contemporânea, 2021)
China is now the largest trading country in the world, accounting for more than 14% of the world economy and with a total external trade of more than 4.5 trillion dollars in 2019. However, recent studies have shown that China’s performance in international trade followed patterns of the world’s economic globalization. This is to say that, although China managed to become the largest manufacture exporter, a considerable amount of its export economy is fruit of foreign investments and processing companies that added little to its domestic value chain. This poses questions on the real impact of the export sector in China’s economy.In this paper, we try to answer the following questions: How exactly does the export sector contribute to China’s development? What is the domestic participation in Chinese high-tech exports? What do the current trends mean for the Chinese export economy? Understanding the participation of indigenous enterprises in the high-tech export sector allows us to grapple with Global Value Chain’s changing dynamics and the forces behind the structural transformation of the Chinese economy, from a labor-intensive commodity exporter towards an innovation-driven high-tech developer.Upon analyzing current literature and using data gathered from China’s National Bureau of Statistics, from 2004 to 2019, our findings support the interpretation that foreign-invested enterprises are losing ground at the same time that the high-tech sector achieves a greater innovative push. Materialized in the Made in China 2025 policy, Chinese high-tech exports are changing, qualitatively speaking. This is evidence of domestic firms taking over the high-tech sector, which represents several implications.First, because there is a negative correlation between the number of processing and foreign-invested firms and innovative initiatives in the domestic market, this process of substitution could signal that the domestic economy will benefit more and absorb more the technology that was concentrated in the high-tech export sector. Second, it reveals that China’s industrial policy is affecting and reshaping the export economy. Third, this possibly implies that investments in education and innovation are generating fruitful results. Finally, it demonstrates that the internationalization of a country’s economy can be simultaneous to the strengthening of its domestic high-tech industry. From governmental push to private entrepreneurship, the high-tech exports sector is fast restructuring to accommodate new dynamics derived from China’s recent economic development. Nevertheless, the export economy is still highly dependent on foreign-invested enterprises and processing firms. The challenge for China now is to support a more robust industrial policy that qualitatively modifies its export sector to boost national innovation and economic spillovers without igniting a backlash from international markets. Along with this challenge, the soaring of labor wages in China, the pandemic, the dual circulation model, and the idea of decoupling from Western countries will tend to reinforce the tendency of domestic takeover of high-tech exports witnessed since 2004.